Accompanying effects of sewage sludge and pine needle biochar with selected organic additives on the soil and plant variables. (November 2022) - Fatima, Bushra; Bibi, Farhana; Ishtiaq Ali, Muhammad; Woods, Jeremy; Ahmad, Mushtaq; Mubashir, Muhammad; Shariq Khan, Mohd; Bokhari, Awais; Khoo, Kuan Shiong
Graphical abstract: Highlights: Use of agricultural bio-waste and municipal solid waste for biochar production. Low-temperature biochar derived from various feedstocks was assessed. Selection of compost, manure fertilizer and algae biomass as organic fertilizer. Biochar has sequestered carbon and acted as sink to optimize nutrient level in soil. Pine needle derived biochar with additive has increased performance in plant growth. Abstract: The effects of synthetic fertilizer and nutrient leaching are causing serious problems impacting soil function and its fertility. Mitigation of nutrient leaching and use of chemical fertilizer is crucial as fertile land adds up sustainability to climate changes. Biochar produced from agricultural bio-waste and municipal solid waste has been used for crop production and when applied in combination with organic nutrients may support mitigation of nutrient loss and adverse effects of chemical fertilizers. Different types of biochar and their application for soil enhancement have been observed, pine needle and sewage sludge derived low-temperature biochar along with compost, organic fertilizer in the form of manure and microalgal biomass may interact with soil chemistry and plant growth to impact nutrient loss and compensate the hazardous effect of chemical fertilizer, but it has not been investigated yet. This present study elaborates application of sewage sludge and pine needle biochar produced at 400 °C in an application rate of 5 % w/w and 10 t h −1 in combination with compost, manure and microalgal biomasses of Closteriopsis acicularis (BM1) and Tetradesmus nygaardi (BM2) on the growth of Chickpea ( Cicer arietinum ) and Fenugreek ( Trigonella foenum-graecum ) crop assessed in a pot experiment over a two crop (Chickpea - Fenugreek) cycle in Pakistan. Results depict that the pine needle biochar with additives has increased plant height by 104.1 ± 2.76 cm and fresh biomass by 49.9 ± 1.02 g, buffered the soil pH to 6.5 for optimum growth of crops and enhance carbon retention by 36 %. This study highlights the valorization of sewage sludge and pine needle into biochar and the effect of biochar augmentation, its impact on soil nutrients and plant biomass enhancement. The greener approach also mitigates and helps in the sustainable management of solid wastes.